Flexibility and Freedom: A Comprehensive Study of Distance Education in 21st Century at Higher Education in Pakistan (Journal of Social Sciences Review, 2025)
The student's point of view about the extent of independence they could enjoy and the flexibility characteristics of distance education in Pakistan higher education were the focal points of the research hereby presented. The study intended to estimate distance students' opinions about their learning experiences and the extent of their involvement in online education. By using a quantitative survey design, this research was specifically focused on students' experiences and viewpoints from the most significant distance programs in the academic field in Pakistan. Of the survey participants, 183 completed the survey and returned the same. The data gathering instrument was a pretested questionnaire containing 16 close-ended questions measured on a 4-point Likert scale. The questionnaire mostly consisted of questions which revealed four domains of the distance learning experience: flexibility and convenience, engagement and interaction, technical support and infrastructure and perceived quality and career relevance. The computable data was processed in SPSS-25.0, where descriptive statistics were computed from survey data, and the analysis included frequency distributions, percentages, mean scores and standard deviations. The results showed a high level of agreement among the students regarding distance education convenience and accessibility. Perceptions of engagement were moderately positive, with a majority believing online learning could be as engaging as traditional classrooms, although concerns were noted regarding peer community and assessment accuracy. The recommendations proposed aimed to guide higher education institutions in Pakistan in optimizing their distance education programs to better meet student needs and expectations.
Keywords: Distance Education; Online Learning; Flexibility; Accessibility; Learning Experience